2013
DOI: 10.1016/j.compedu.2012.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Exploring asynchronous and synchronous tool use in online courses

Abstract: While the independent contributions of synchronous and asynchronous interaction in online learning are clear, comparatively less is known about the pedagogical consequences of using both modes in the same environment. In this study, we examine relationships between students' use of asynchronous discussion forums and synchronous private messages (PM). We find that asynchronous notes contain more academic language and less social language, are more difficult to read, and are longer compared to PM. In addition, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(116 citation statements)
references
References 34 publications
3
107
0
6
Order By: Relevance
“…Synchronous forums, although usually more informal, are useful for the exchange of rapidly-evolving ideas (e.g. debates) and are also more suited to increasing social presence and therefore filling the social void in the absence of face-to-face interaction (Oztok et al, 2013). I came to appreciate that socialisation plays an important role in allowing relationships to form and provides a foundation for learning.…”
Section: Evaluation Of Learning Experiencementioning
confidence: 99%
“…Synchronous forums, although usually more informal, are useful for the exchange of rapidly-evolving ideas (e.g. debates) and are also more suited to increasing social presence and therefore filling the social void in the absence of face-to-face interaction (Oztok et al, 2013). I came to appreciate that socialisation plays an important role in allowing relationships to form and provides a foundation for learning.…”
Section: Evaluation Of Learning Experiencementioning
confidence: 99%
“…For example, Brown and Green (2009) calculated time spent reading discussions by extracting the average number of words per discussion and then multiplying it by 180 words per minute (which was obtained empirically). The challenge with this approach is in its inability to detect shallow reading and skimming (i.e., reading that is faster than 6.5 words per second) (Hewitt, Brett, & Peters, 2007), as done in similar studies (Oztok, Zingaro, Brett, & Hewitt, 2013;Wise, Speer, et al, 2013;Wise, Zhao, et al 2013b) that estimated timeon-task from trace-data. Some studies also used self-reported data on the amount of time students spent using the system (e.g., García-Martín & García-Sánchez, 2013;Hsu & Ching, 2013;Romero & Barbera, 2011), and this approach raises an additional set of reliability challenges (Winne & Jamieson-Noel, 2002).…”
Section: Web Usage Mining In Distance Educationmentioning
confidence: 99%
“…The use of asynchronous tools might, however, have both advantages and disadvantages. A study by Oztok, Zingaro, Brett and Hewitt (2013) shows that the students' use of synchronous tools, such as private messages, were shorter, but also easier to read than public messages. However, in the case of the two courses analyzed in the present study, synchronous tools were primarily used for communication and not for assignments.…”
Section: Progressive Literary Learningmentioning
confidence: 99%